2004
DOI: 10.2118/04-12-02
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Sand Structures Surrounding A Horizontal Well Slot During Cold Production

Abstract: A better understanding of the flow of sand and oil into slotted horizontal well liners is important for both thermal and non-thermal heavy oil production. The objective of this study was to investigate the structures that might form in and around a slot when sand production stops, and to relate the development of these structures to the porosity and, therefore, permeability increases within the sand pack. The parameters studied were slot size, sand morphology, and grain size distribution. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An analysis of the sand-production data from the previous air tests indicated that there was no obvious trend between sand production and the sorting of the sand (as represented by the uniformity coefficient) or between sand production and the sandgrain morphology (Meza-Diaz et al 2003, 2004. This is shown graphically in Figs.…”
Section: Experimental Conditions and Parameter Selectionmentioning
confidence: 94%
See 1 more Smart Citation
“…An analysis of the sand-production data from the previous air tests indicated that there was no obvious trend between sand production and the sorting of the sand (as represented by the uniformity coefficient) or between sand production and the sandgrain morphology (Meza-Diaz et al 2003, 2004. This is shown graphically in Figs.…”
Section: Experimental Conditions and Parameter Selectionmentioning
confidence: 94%
“…The results of previous sand-production experiments using air as the working fl uid (Meza-Diaz et al 2003, 2004 were used to guide the selection of the range of slot widths for the experiments reported in this study. The air tests provided sand-production data across several slot sizes for various sands that possessed different grain-size distributions and morphologies (shapes).…”
Section: Experimental Conditions and Parameter Selectionmentioning
confidence: 99%